Implementation of Preparation of Financial Reports of MSMEs Based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) Case Study at CV Hubol's - Adventus Lumban Siantar; Dwi Saraswati (International Journal of Integrative Sciences, 2024)
The topic of this research is "Implementation of Financial Report Preparation for MSMEs Based on Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) Case Study at CV Hubol's". The aim is to identify the obstacles faced by CV Hubol's in preparing financial reports and how to prepare them in accordance with SAK EMKM. This study uses a qualitative approach and descriptive methodology. The results of the study indicate that CV Hubol's financial reports are still simple and are only based on product sales. In addition, CV Hubol has not complied with SAK EMKM due to the lack of information and skilled human resources in preparing reports according to standards. The data from this study are expected to help MSME CV Hubol in implementing SAK EMKM